An assessment of a municipal physical activity programme for seniors based on the EFQM model: Integrating the views of internal and external stakeholders. (June 2020) - Moura e Sá, Patrícia; Fernandes, Carolina
Highlights: Doing exercise on a regular basis can mitigate many negative consequences of ageing processes. Research on the assessment of physical activity programmes from a TQM point of view is scarce. The EFQM model measures programme performance according to the views of different stakeholders. Customer satisfaction and loyalty, clarity of programme mission and strategy are main areas of strength. Insufficient attention to the measurement of people satisfaction is one of the key areas for improvement. Abstract: The growing proportion of senior citizens and the importance of encouraging active well-ageing behaviours explain the increasing efforts carried out by governments to develop exercise programmes particularly targeted to this group. The complexity associated with the running of these programmes and the resources committed make their quality assessment essential. The aim of the current paper is to validate and refine the use of the EFQM model in this context. A programme of a medium-sized municipality of the Centre region of Portugal was used as a case study to evaluate the adequacy and relevance of the EFQM model and to identify the strengths and weaknesses of the current programme based on the data collected from service users, instructors, municipal leaders and programme partners. High levels of customer satisfaction and loyalty, together with the clarity of programme mission and strategy emerged as main areas of strength. On the other hand, insufficient attention to the measurement of people satisfaction, as well as the leaders' failure of to show appreciation for the efforts developed by the programme instructors are key areas for improvement.